Kajian Tingkat Erosi pada Penggunaan Lahan Kelapa Sawit (Elaeis guineensis Jack) di Sub DAS Tapung Kiri (Jurnal Agro Teknologi Tropika, 2012)
The objective of this research is to observe the erodibility of Sub DAS Tapung Kiri at the Kelapa sawit land systemin Rokan Hulu District and Kampar District. Besides that, the purpose of the research is to know the dominant factorsthat influence the erotion value. The research used surver nethod based on information graphis overlay map with theland unit system, overlay topographic map interpretation, land map system and soil map. The value of erodibility scoresusing prediction erodibility USLE RKLSCP and regression analyses backward elimination to study the dominant factorinfluenced erodibility values. The result showed that there was a variation of TBE on Sub DAS Tapung Kiri with the palmof land system which classified as i.e. low, midlle, and high the highest index of erodibility was found at location 4(Petapahan 2) 15,5. Based on analysis regression backward elimination, there were two dominant factors found: slopelength factor and erodibility factor.Keywords: Erotion, USLE, Sub DAS Tapung